Acceptability of Mango Seed Kernel (Mangifera Indica) as Potential Tea Source - Reynald P. Alican (Research Synergy Foundation, 2024)
This study determined the acceptability and phytochemical properties of mango seed kernel (Mangifera Indica) as a tea source. Kernels from Carabao, Apple, and Indian Mango seeds were used in the study, which involved four drying processes: 7, 14, 21, and 28 days. The hedonic scale method was used to determine the mean level of acceptability of the tea, which was evaluated by the panelists. The presence of DPPH scavenging activity, total flavonoids, phenols, tannins, and anthocyanins was analyzed for phytochemical analysis. Statistical analysis, including mean and standard deviation, was used to evaluate acceptability levels, and ANOVA was used to determine significant differences. The results revealed that tea derived from Carabao mango kernels dried for 7 days had the highest acceptability. The phytochemical analyses of Carabao mango powder showed DPPH scavenging activity, flavonoids, phenols, and tannins; however, anthocyanins were not detected. The findings indicate that there were no significant differences in the mean sensory evaluation of the Carabao Mango kernel tea samples in terms of color, odor, taste, and general acceptability. In contrast, significant differences were observed among Apple Mango kernel tea samples for color and odor, while no significant differences were found for taste and general acceptability. Similarly, significant differences were noted among the samples of Indian Mango kernel tea for color but not for odor, taste, and general acceptability. The study highlights the potential of using mango seed kernels for tea production, thereby contributing to waste reduction and promoting health-conscious food production and consumption practices.